2021
DOI: 10.1038/s41597-021-01026-2
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Open-access quantitative MRI data of the spinal cord and reproducibility across participants, sites and manufacturers

Abstract: In the original version of this Data Descriptor, the legend to Figure 16 incorrectly stated that the figure depicts the results of the multi-subject study for the MT protocol and that the mean MTR was computed. The legend has now been corrected to indicate that the figure depicts the results of the multi-subject study for the DWI scan and that the FA was computed. This has now been corrected in the PDF and HTML versions of the Data Descriptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Here, we found that the inter-site CoV of CSA ranged between 2.90% and 5.76%, which is reasonably low. Comparing these results with reliability of directly acquired MRI, the inter-site repeatability of cord segmentation across different MRI systems and protocols was recently addressed in a multicenter study including 42 sites across the world ( Cohen-Adad et al, 2021 ). This study reported inter-site CoV of CSA based on acquired T 1 -w images (including MPRAGE) separately for different MRI vendors, which ranged between 3.08% and 4.41% being comparable to the results obtained from synT 1 -w in our study.…”
Section: Intra-and Inter-site Repeatabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we found that the inter-site CoV of CSA ranged between 2.90% and 5.76%, which is reasonably low. Comparing these results with reliability of directly acquired MRI, the inter-site repeatability of cord segmentation across different MRI systems and protocols was recently addressed in a multicenter study including 42 sites across the world ( Cohen-Adad et al, 2021 ). This study reported inter-site CoV of CSA based on acquired T 1 -w images (including MPRAGE) separately for different MRI vendors, which ranged between 3.08% and 4.41% being comparable to the results obtained from synT 1 -w in our study.…”
Section: Intra-and Inter-site Repeatabilitymentioning
confidence: 99%
“…This study reported inter-site CoV of CSA based on acquired T 1 -w images (including MPRAGE) separately for different MRI vendors, which ranged between 3.08% and 4.41% being comparable to the results obtained from synT 1 -w in our study. However, we neither separated the different MRI systems nor averaged the CSA measurements across sev-eral vertebral levels in our analysis which needs to be considered when comparing these studies ( Cohen-Adad et al, 2021 ;Weeda et al, 2019 ).…”
Section: Intra-and Inter-site Repeatabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The MRI scanner acquisition parameters, including voxel size and slice thickness for the T2-weighted axial sequence, were collected and the aT2w sequence for each patient was converted into a series of JPEG images (Cervical SCI Dataset). All images from Spine Generic Dataset [15] were resized into 320x320 pixels to standardize input size and computational e ciency. We standardized the color range between various MRI images with contrast stretching.…”
Section: Data Pre-processingmentioning
confidence: 99%